The Role of Coalitions in the Health and Well-Being of Farmworkers - Ashlyn Michael; LaToya O'Neal; Reagan Anderson; Beatrice Pierre; Tracy Irani (EDIS)
Farmworker coalitions provide an informal, non-governmental path for farmers and farmworkers to assemble and advocate for their rights in a safe and accessible manner. This publication aims to educate established entities such as Extension on the importance of farmworker coalitions and their role in the facilitation and development of these coalitions. Written by Ashlyn Michael, LaToya O’Neal, Reagan Anderson, Beatrice Pierre, and Tracy Irani, and published by the UF/IFAS Department of Family, Youth and Community Sciences, September 2022.